Isolation and Properties of a β-Alanine Transaminaseless Mutant of Pseudomonas fluorescens - Hechtman, P. (1970)
β-Alanine catabolism in Pseudomonas fluorescens is initiated by the enzyme β-alanine transaminase. We have isolated mutants which fail to produce this enzyme and thus cannot grow on β-alanine as the sole nitrogen source. The accumulation of β-alanine-1-(14)C has been studied in one of these mutants, strain 67, and in the wild type. In the mutant, β-alanine remains in a stable intracellular pool, whereas in the wild type conversion of β-alanine to an intermediate, presumably malonate semialdehyde, and to CO(2) can be detected. The membrane transport system for β-alanine can be conveniently studied in this transaminaseless mutant.